Business Improvement of Virgin Coconut Oil (VCO) in Jember Lor Village, Patrang District, Jember Regency - Nely Supeni; Mainatul Ilmi; Saiful Amin (Trescode Green Organization, 2023)
This time the Community Partnership Program (PKM) partners are Home Industries (IRT), namely Virgin Coconut Oil (VCO) Entrepreneurs. VCO is oil produced from pure coconut through a fermentation process, without using preservatives. The benefits of this oil in addition to maintaining health and stamina, can also cure all kinds of diseases. Besides being drinkable, this VCO can be used as an external medicine, namely as a topical medicine for wounds on the body. The problems faced by PKM partners this time are as follows: 1) The equipment for the VCO production process is still limited. The grated coconut used to grate coconut meat is still traditional, namely manual coconut grater. 2) There is no proper recording of financial statements in order to know the profit/loss of VCO oil production business. Thus, Mr. Agung's VCO oil production business requires: 1) Procurement of an electric coconut grater 2) Mentoring for the preparation of financial reports.